Pelestarian Budaya Tahlil Kepada Anak Muda Melalui Organisasi IPNU-IPPNU Di Kecamatan Puring - Febriany, Febriany; Zahna, Lutfi Raizatul; Nisa, Istiti Sakinatun; Sari, Reza Kurnia Citra (IAINU Kebumen, 2024)
The preservation of the tahlil tradition among young people through the IPNU-IPPNU organization in Puring District is an important effort to maintain a long-standing religious tradition in the community. Tahlil, which consists of the recitation of